Effect of the Improved Pall Friction Damper on the Seismic Response of Steel Frames - Sarjou, P. H.; Shabakhty, N. (Engineering, Technology & Applied Science Research, 2017)
Energy-absorbing dampers are used to reinforce structures which are vulnerable to earthquakes. This study evaluates the performance of Improved Pall Frictional Dampers (IPFD) which is a type of Pall Frictional Damper (PFD). For this purpose, this study compares the performances of steel frames with concentric steel bracing reinforced by IPFD and steel frames with concentric steel bracing with no damper. Frames with different stories and pans were modelled in sap2000 and exposed to accelerograms of earthquakes for non-linear time history analysis. Results of analysis were studied; parameters such as story displacement, base shear and absorbed energy were compared in steel frames with damper and without damper.